China's Economic Diplomacy and the Politics-Trade Nexus - Andreas Fuchs (University of Heidelberg, Department of Economics, 2016)
This article reviews the literature on the linkages between political tensions, economic diplomacy and international trade in the light of China's rise in the global economy. The existing scholarly work suggests that economic diplomacy should be more pivotal in economic exchange with China than with Western market economies. In an econometric test, I analyze how diplomatic tensions, measured through foreign dignitaries' meetings with the Dalai Lama, affect the likelihood of an official visit from a Chinese leader. The results show that the likelihood of the Chinese leadership traveling to a country is 13.6 percent lower if the country's government receives the Dalai Lama in a given year but increases in the following year, supposedly to restore ties. This finding underlines that economic diplomacy is an important channel linking political climate and economic exchange between nations.
urn:nbn:de:bsz:16-heidok-203777
Keywords: 330; economic diplomacy; international trade; embassies; political climate; state visits; leadership travel; emerging economies; China; Dalai Lama; Tibet; Außenpolitik; Internationale Wirtschaftsbeziehungen; Internationale Beziehungen; China